LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS FROM FISHING FAMILIES: A QUALITATIVE ANALYSIS - Irma Octaviani Irma; Ana Andriani Andriani; Y. Suyitno Suyitno; Wakhudin Wakhudin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Learning motivation is a major factor in student success, especially for children from fishing families who are influenced by socioeconomic conditions, family environment, and coastal culture. This study aims to analyze the learning motivation of students from fishing families in elementary schools within a cluster in the coastal area of South Cilacap, as well as the factors that influence it. The study used a qualitative, phenomenological approach. The research subjects consisted of students, teachers, and parents, selected purposively to represent variations in learning conditions and family support. Data were collected through observation, interviews, and documentation. Data were analyzed through condensation, presentation, and verification of conclusions. We ensured the validity of the findings by triangulating techniques and sources. The results of the study indicate variations in learning motivation influenced by internal factors (drive to achieve, interest, and awareness of learning goals, and curiosity) and external factors (parental support, teacher attention, family socioeconomic conditions, and the school environment). Students who are highly motivated demonstrate determination, a willingness to learn, discipline, and an understanding of the importance of education. Moderate motivation is evident in fluctuating learning enthusiasm and reliance on external stimuli such as praise and grades from teachers and parents. Low motivation is characterized by passive behavior, lack of focus, minimal internal and external support, inconsistent attendance, and a lack of recognition of school as a top priority. This study confirms that the learning motivation of fishermen's children depends not only on family finances but also on moral, emotional, and social support from their surrounding environment. The active roles of teachers and parents are crucial for fostering students' sustained enthusiasm for learning in coastal schools.